Applications of the hollow-fibre infection model (HFIM) in viral infection studies. (22nd November 2022) - Kembou-Ringert, Japhette E; Readman, John; Smith, Claire M; Breuer, Judith; Standing, Joseph F
Abstract: Conventional cell culture systems involve growing cells in stationary cultures in the presence of growth medium containing various types of supplements. At confluency, the cells are divided and further expanded in new culture dishes. This passage from confluent monolayer to sparse cultures does not reflect normal physiological conditions and represents quite a drastic physiological change that may affect the natural cell physiobiology. Hollow-fibre bioreactors were in part developed to overcome these limitations and since their inception, they have widely been used in production of monoclonal antibodies and recombinant proteins. These bioreactors are increasingly used to study antibacterial drug effects via simulation of in vivo pharmacokinetic profiles. The use of the hollow-fibre infection model (HFIM) in viral infection studies is less well developed and in this review we have analysed and summarized the current available literature on the use of these bioreactors, with an emphasis on viruses. Our work has demonstrated that this system can be applied for viral expansion, studies of drug resistance mechanisms, and studies of pharmacokinetic/pharmacodynamic (PK/PD) of antiviral compounds. These platforms could therefore have great applications in large-scale vaccine development, and in studies of mechanisms driving antiviral resistance, since the HFIM could recapitulate the same resistance mechanisms and mutations observed in vivo in clinic. Furthermore, some dosage and spacing regimens evaluated in the HFIM system, as allowing maximal viral suppression, are in line with clinical practice and highlight this ' in vivo -like' system as a powerful tool for experimental validation of in vitro -predicted antiviral activities.